Implementação da Política Nacional para População em Situação de Rua: uma análise sob a perspectiva dos arranjos institucionais e das capacidades estatais (2009-2020) - Baroni, William (Universidade Federal de São Carlos, 2021)
This work aimed to comprehend the process of implementation of the National Policy for the Homeless Population considering the institutional arrangement in which it is inserted, and the identification of the state capabilities that were generated through them, and how it affected the process of implementation, given the observed results. For this, we began by presenting the main characteristics of the homeless population, approaching the repressive treatment that this population has received by the State throughout history. The higher marks of the trajectory of the fight of this population seeking recognition and achievement of rights were presented. Moreover, the process of the entrance of the demands of this population into the governmental agenda and the process of building the National Policy for the Homeless Population was also discussed. A brief discussion about the public policies and the concept of state capabilities was also performed, presenting a model for analyzing these capabilities. Following the model presented, firstly, the objectives and goals of the policy were identified, so the institutional arrangement was mapped, considering the actors, institutions, and relationships present in the process of implementing this policy. Based on the institutional arrangement mapped, the generated state capacities were identified and analyzed, being this analysis based on the results already identified with this policy implementation. As a way of data collection, the documentary research was performed in legislation and government databases. Based on the analysis performed, it was found that the capacities generated were enough to meet most of the objectives and goals of the National Policy for the Homeless Population. Besides that, it was observed a serious risk of regression with the freeze measures of the social spending and with the reduction of the user’s participation during monitoring the implementation of this policy, which can negatively impact the state capabilities.
Implementation of National Policy for the Homeless Population: an analysis from the perspective of institutional arrangements and state capacities (2009-2020)
Keywords: Capacidades estatais; População em situação de rua; Implementação de políticas públicas; State capabilities; Homeless population; Implementation of public policies; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA::ORGANIZACOES PUBLICAS